New genomic regions in dry bean (Phaseolus vulgaris L.) associated with stem diameter, plant height, and other plant architecture traits - Oscar Rodríguez; Jayanta Roy; Philip E. McClean; Didier Murillo; Kristin Simons; Nusrat Khan; Jose C. Figueroa-Cerna; Juan M. Osorno (Euphytica, 2026)
Growth habit is one of the most important domestication traits in dry bean ( Phaseolus vulgaris L.). In the U.S. for example, Type II indeterminate upright plant varieties have allowed farmers to switch from historic two-pass harvest to one-pass direct harvest. Previous work suggested a stem diameter of 5.6 mm as threshold to select Type II architecture genotypes suitable for direct combining. This study aimed to validate the correlation between stem diameter and other agronomic traits using lines comprising various market classes from a public breeding program. It also assesses if stem diameter could be used to select genotypes that combine high seed yield and upright architecture. GWAS was also used to identify genomic regions related to plant height and stem diameter. Mean stem diameter among breeding lines was 7.7 mm, higher than the proposed threshold. Stem diameter showed no significant G × E interactions, with the highest broad-sense heritabilities observed for regular-darkening pinto (pinto) and slow darkening (SD) pinto. Plant height was the most relevant trait for seed yield variation in black, great northern, and navy beans. In contrast, both plant height and stem diameter are required to explain part of seed yield variability and selecting upright plants for pinto, red/pink, and SD-pinto. GWAS revealed significant regions located on chromosomes Pv03, Pv07, and Pv11 depending on trait and race used. A region near 40.7 Mb on Pv07 was associated with both plant height and stem diameter, suggesting further studies on indeterminate upright dry bean plant architecture should focus on this region.

Freshwater biodiversity in a rapidly changing Arctic: An expert horizon scan of key research questions - Joseph M. Culp; Michael Power; Kirsten S. Christoffersen; Willem Goedkoop; Kimmo K. Kahilainen; Milla Rautio; Fernando Chaguaceda; Marie-Pier Hébert; Sanne M. Moedt; Dermot Antoniades; Simon Belle; Daniel Bolnick; et al. (Ambio, 2026)
Arctic freshwater biodiversity is rapidly changing due to climate warming, resource extraction, infrastructure development, and landscape transformation. To improve understanding, predict future responses, and inform policy formulation, research needs must be clearly identified. Using a horizon scan survey, Arctic freshwater experts from government, international agencies, and Indigenous Peoples identified 77 biodiversity research questions with 17 highlighted as most important for near term assessment. These questions span nine thematic categories: biodiversity and taxonomic challenges, hydrological change, productivity and food webs, ecosystem connectivity, methods, monitoring and assessment, permafrost change, winter ecology, anthropogenic development, and Indigenous Knowledge. Climate change emerged as the major driver among all categories and research questions. A key priority identified was the urgent need for long-term, harmonized monitoring programs among Arctic countries. Multiple knowledge gaps detected suggest that circumpolar research collaborations are required to tackle these issues.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Fine mapping and identification of causal alleles at the Ur-11 locus controlling rust resistance in common bean (Phaseolus vulgaris L.) - Mohammad Erfatpour; Kristin J. Simons; Jayanta Roy; Jose C. Figueroa-Cerna; Rian Lee; James Beaver; Phillip E. McClean; Juan M. Osorno (Theoretical and Applied Genetics, 2025)
The Middle American rust resistance gene Ur-11 present in common bean ( Phaseolus vulgaris L.) confers resistance to all but one known race of the pathogen Uromyces appendiculatus (Pers.) Unger. Even though progress has been made in understanding the host–pathogen interactions between common bean and U. appendiculatus , the causal alleles of the majority of rust resistance loci, including Ur-11, remain unknown. A genome-wide association study (GWAS) was conducted to identify genomic regions associated with resistance to the U. appendiculatus race 31–22, which is avirulent to Ur-11 but virulent to other Middle American rust resistance genes. GWAS using genotypic data consisting of approximately 70,959 SNP markers and phenotypic data based on the median reaction type (1–9 scale) of a panel of 357 Middle American breeding lines and cultivars, plus 5 germplasm lines with the Ur-11 locus derived from PI 181996, located Ur-11 on chromosome Pv11. Twenty-seven SNP markers clustered in the 55.16–55.56 Mb region of the P. vulgaris UI111 reference. Multiple DNA sequence alignments detected a missense mutation [c.1,328A > G] in the PvUI111.11G202400 gene model that encodes a leucine-rich repeat-containing protein in response to race 31–22. A PCR allele competitive extension marker (PACE) was developed and tested across a panel of ~ 700 Middle American dry bean genotypes. No recombination event was observed for the PACE marker among the tested genotypes; suggesting that the polymorphism on which it is based is very close to or in the Ur-11 gene. This PACE marker will be a useful and reliable marker for marker-assisted selection of Ur-11 -based resistance to bean rust.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Improving water quality in a hypereutrophic lake and tributary through agricultural nutrient mitigation: A Multi-year monitoring analysis - Barry Husk; Paul Julian; Dana Simon; Nicolas Tromas; Dawson Phan; Kristin Painter; Helen Baulch; Sébastien Sauvé (Journal of Environmental Management, 2024)

Selective recovery of silver ions from copper-contaminated effluents using electrodialysis - Pauline Zimmermann; Kristin Wahl; Önder Tekinalp; Simon Birger Byremo Solberg; Liyuan Deng; Øivind Wilhelmsen; Odne Stokke Burheim (Desalination, 2024)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Reconciling Behavioural, Bioenergetic, and Oceanographic Views of Bowhead Whale Predation on Overwintering Copepods at an Arctic Hotspot (Disko Bay, Greenland) - Neil S. Banas; Eva Friis Møller; Kristin L. Laidre; Malene Simon; Ingrid H. Ellingsen; Torkel Gissel Nielsen (Frontiers in Marine Science, 2021)
Bowhead whales ( Balaena mysticetus ) visit Disko Bay, West Greenland in winter and early spring to feed on Calanus spp., at a time of year when the copepods are still mostly in diapause and concentrated in near-bottom patches. Combining past observations of copepod abundance and distribution with detailed observations of bowhead whale foraging behaviour from telemetry suggests that if the whales target the highest-density patches, they likely consume 26–75% of the Calanus standing stock annually. A parallel bioenergetic calculation further suggests that the whales' patch selection must be close to optimally efficient at finding hotspots of high density copepods near the sea floor in order for foraging in Disko Bay to be a net energetic gain. Annual Calanus consumption by bowhead whales is similar to median estimates of consumption by each of three zooplankton taxa (jellies, chaetognaths, and predatory copepods), and much greater than the median estimate of consumption by fish larvae, as derived from seasonal abundance and specific ingestion rates from the literature. The copepods' self-concentration during diapause, far from providing a refuge from predation, is the behaviour that makes this strong trophic link possible. Because the grazing impact of the whales comes 6–10 months later than the annual peak in primary production, and because Disko Bay sits at the end of rapid advective pathways (here delineated by a simple numerical particle-tracking experiment), it is likely that these Calanus populations act in part as a long-distance energetic bridge between the whales and primary production hundreds or thousands of km away.

Seasonal detections of bearded seal (Erignathus barbatus) vocalizations in Baffin Bay and Davis Strait in relation to sea ice concentration - Tenna K. Boye; Malene J. Simon; Kristin L. Laidre; Frank Rigét; Kathleen M. Stafford (Polar Biology, 2020)

Personalising drug safety—results from the multi-centre prospective observational study on Adverse Drug Reactions in Emergency Departments (ADRED) - Katja S. Just; Harald Dormann; Miriam Böhme; Marlen Schurig; Katharina L. Schneider; Michael Steffens; Sandra Dunow; Bettina Plank-Kiegele; Kristin Ettrich; Thomas Seufferlein; Ingo Gräff; Svitlana Igel; et al. (European Journal of Clinical Pharmacology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Many eyes on the ground: citizen science is an effective early detection tool for biosecurity - Melissa L. Thomas; Nihara Gunawardene; Kristin Horton; Angus Williams; Simon O’Connor; Simon McKirdy; Johann van der Merwe (Biological Invasions, 2017)

Human centromere repositioning within euchromatin after partial chromosome deletion - Lori L. Sullivan; Kristin A. Maloney; Aaron J. Towers; Simon G. Gregory; Beth A. Sullivan (Chromosome Research, 2016)

Geographic and temporal dynamics of a global radiation and diversification in the killer whale - Phillip A. Morin; Kim M. Parsons; Frederick I. Archer; María C. Ávila‐Arcos; Lance G. Barrett‐Lennard; Luciano Dalla Rosa; Sebastián Duchêne; John W. Durban; Graeme M. Ellis; Steven H. Ferguson; John K. Ford; Michael J. Ford; et al. (Molecular Ecology, 2015)
Global climate change during the Late Pleistocene periodically encroached and then released habitat during the glacial cycles, causing range expansions and contractions in some species. These dynamics have played a major role in geographic radiations, diversification and speciation. We investigate these dynamics in the most widely distributed of marine mammals, the killer whale ( Orcinus orca ), using a global data set of over 450 samples. This marine top predator inhabits coastal and pelagic ecosystems ranging from the ice edge to the tropics, often exhibiting ecological, behavioural and morphological variation suggestive of local adaptation accompanied by reproductive isolation. Results suggest a rapid global radiation occurred over the last 350 000 years. Based on habitat models, we estimated there was only a 15% global contraction of core suitable habitat during the last glacial maximum, and the resources appeared to sustain a constant global effective female population size throughout the Late Pleistocene. Reconstruction of the ancestral phylogeography highlighted the high mobility of this species, identifying 22 strongly supported long‐range dispersal events including interoceanic and interhemispheric movement. Despite this propensity for geographic dispersal, the increased sampling of this study uncovered very few potential examples of ancestral dispersal among ecotypes. Concordance of nuclear and mitochondrial data further confirms genetic cohesiveness, with little or no current gene flow among sympatric ecotypes. Taken as a whole, our data suggest that the glacial cycles influenced local populations in different ways, with no clear global pattern, but with secondary contact among lineages following long‐range dispersal as a potential mechanism driving ecological diversification.

Cascading effects of generalist fish introduction in oligotrophic lakes - Kristin E. Strock; Jasmine E. Saros; Kevin S. Simon; Suzanne McGowan; Michael T. Kinnison (Hydrobiologia, 2013)

Plastid division control: the PDV proteins regulate DRP5B dynamin activity - Ingrid Holtsmark; Sungsu Lee; Kristin Aaser Lunde; Kathrine Auestad; Jodi Maple-Grødem; Simon Geir Møller (Plant Molecular Biology, 2013)

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

A radiation hybrid map of chromosome 1D reveals synteny conservation at a wheat speciation locus - Monika K. Michalak de Jimenez; Filippo M. Bassi; Farhad Ghavami; Kristin Simons; Rissa Dizon; Raed I. Seetan; Loai M. Alnemer; Anne M. Denton; Münevver Doğramacı; Hana Šimková; Jaroslav Doležel; Kiran Seth; et al. (Functional & Integrative Genomics, 2013)

Cell cycle arrest associated with anoxia-induced quiescence, anoxic preconditioning, and embryonic diapause in embryos of the annual killifish Austrofundulus limnaeus - Camie L. Meller; Robert Meller; Roger P. Simon; Kristin M. Culpepper; Jason E. Podrabsky (Journal of Comparative Physiology B, 2012)

Agricultural by-products provide critical habitat components for cold-climate populations of an oviparous snake (Natrix natrix) - Kristin Löwenborg; Simon Kärvemo; Alma Tiwe; Mattias Hagman (Biodiversity and Conservation, 2012)

Genetic mapping of stem rust resistance gene Sr13 in tetraploid wheat (Triticum turgidum ssp. durum L.) - Kristin Simons; Zewdie Abate; Shiaoman Chao; Wenjun Zhang; Matt Rouse; Yue Jin; Elias Elias; Jorge Dubcovsky (Theoretical and Applied Genetics, 2011)

Survey of Grauer's Gorillas (Gorilla gorilla graueri) and Eastern Chimpanzees (Pan troglodytes schweinfurthi) in the Kahuzi-Biega National Park Lowland Sector and Adjacent Forest in Eastern Democratic Republic of Congo - Jefferson S. Hall; Lee J. T. White; Bila-Isia Inogwabini; Ilambu Omari; Hilary Simons Morland; Elizabeth A. Williamson; Kristin Saltonstall; Peter Walsh; Claude Sikubwabo; Dumbo Bonny; Kaleme Prince Kiswele; Amy Vedder; et al. (International Journal of Primatology, 1998)